The multi-epoch X-ray tale of I Zwicky 1 outflows. Issue 4 (9th September 2022) - Rogantini, D; Costantini, E; Gallo, L C; Wilkins, D R; Brandt, W N; Mehdipour, M
ABSTRACT: The narrow-line Seyfert 1 galaxy $\rm I\, \, Zwicky\, 1$ shows a unique and complex system of ionized gas in outflow, which consists of an ultra-fast wind and a two-component warm absorber. In the last two decades, XMM–Newton monitored the source multiple times enabling the study of the long-term variability of the various outflows. Plasma in photoionization equilibrium with the ionizing source responds and varies accordingly to any change of the ionizing luminosity. However, detailed modelling of the past Reflection Grating Spectrometer (RGS) data has shown no correlation between the plasma ionization state and the ionizing continuum, revealing a complex long-term variability of the multiphase warm absorber. Here, we present a new observation of $\rm I\, \, Zwicky\, 1$ by XMM–Newton taken in early 2020 characterized by a lower X-ray flux state. The soft X-ray spectrum from the RGS reveals the two components of the warm absorber with log ξ ∼ −1.0 and log ξ ∼ 1.7. Comparing our results with the previous observations, the ionization state of the two absorbing gas components is continuously changing, following the same unpredictable behaviour. The new results strengthen the scenario in which the ionization state of the warm absorber is driven by the density of the gas rather than the ionizing luminosity. In particular, the presence of a radiation driven, inhomogeneous clumpy outflow may explain both the variability in ionization throughout the years and the line-locked N v system observed in the ultraviolet band. Finally, the EPIC-pn spectrum reveals an ultra-fast wind with an outflow velocity of ∼0.26 c and ionization parameter of log ξ ∼ 3.8.